Anomalies in Bighead Carp Aristichthys nobilis and African Catfish Clarias gariepinus in Biratnagar, Nepal - Subba, B.R. (Our Nature, 2006)
Truncation and deformation on the upper jaw in juvenile and adult respectively in African catfish Clarias gariepinus; and vertebral abnormalities in Bighead carp Aristichthys nobilis are described. Key words: Anomalies, Upper jaw, Caudal fin, Vertebral column, Fishes doi:10.3126/on.v2i1.324 Our Nature (2004) 2: 41-44